An Optimization Method for CCHP and River Water Source Heat Pump Combined System. (July 2018) - Lv, Yuexia; Si, Pengfei; Rong, Xiangyang; Yan, Jinyue
Abstract: Combined Cooling, Heating and Power (CCHP) systems have been widely utilized in the buildings to achieve high efficiency cascade utilization of energy. Heat pump is another widely utilized technology to improve the building energy efficiency. The paper presents a hybrid system which integrates the CCHP with river water source heat pump to combine the advantages of these two technologies. A physical model with energy storage module was firstly developed for the combined system. A case study was further carried out to investigate the optimized configuration and operation performance of the combined system.